Simultaneously achieving high-κ and strong ferroelectricity in Hf0.5Zr0.5O2 thin film by structural stacking design - Yuchen Wang; Jiachen Li; Hansheng Zhu; Haifeng Bu; Xinzhe Du; Shengchun Shen; Yuewei Yin; Xiaoguang Li (Journal of Materiomics, 2025)
The superior dielectric and ferroelectric properties of HfO2-based thin films, coupled with excellent silicon compatibility, position them as highly attractive candidates for dynamic and ferroelectric random-access memories (DRAM and FeRAM). However, simultaneously achieving high dielectric constant (κ) and strong ferroelectricity in HfO2-based films presents a challenge, as high-κ and ferroelectricity are associated with the tetragonal and orthorhombic phases, respectively. In this study, we report both the good ferroelectric and dielectric properties obtained in W/Hf0.5Zr0.5O2 (HZO ∼6.5 nm)/W with morphotropic phase boundary structure by optimizing stacking sequence of HfO2 and ZrO2 sublayers. Notably, by alternating stacking of 1-cycle HfO2 with 1-cycle ZrO2 sublayers ((1–HfO2)/(1–ZrO2)), high-κ (>50) and large polarization (2Pr > 40 μC/cm2, after wake-up) can be achieved. Besides, the (1–HfO2)/(1–ZrO2) stacking configuration presents better thermal stability compared to other stacking sequences. Furthermore, the incorporation of an Al2O3 layer leads to a low leakage current density (<10−7 A/cm2 at 0.65 V) and high dielectric endurance over 1013 cycles (operating voltage ∼0.5 V). A low equivalent oxide thickness (EOT ∼0.53 nm) and considerable polarization with low leakage are simultaneously achieved. These results highlight the potential of HfO2-based films with optimized structural stacking as a trade-off approach for integrating DRAM and FeRAM on one-chip.